Interreligious Encounters in Europe: Sites, Materialities and Practices - Winkler, Jan; Haddad, Laura; Martínez-Ariño, Julia; Mezzetti, Giulia (Routledge, 2023)
This book examines interreligious dialogue in Europe and how interreligious encounters are framed, expressed and practised. Throughout Europe religious identities have increasingly become significant categories within debates on migration, cohesion, diversity and belonging. By focusing on the spatialities, materialities and practices of interreligious dialogues and encounters, the volume sheds light on the heterogeneous domains where the visibility and inclusion of religious and cultural differences are currently negotiated and contested. The chapters draw on social science perspectives and include a range of empirical case studies from a variety of European settings. The contributions (a) shed light on the subjectivities, relations and modes of behaviour produced, negotiated and contested in and through locally embedded interreligious encounters and dialogue-oriented practices, (b) observe the power dynamics that shape those practices and encounters and (c) discuss their implications for the place(s) of religion in the public sphere. Overall the book contributes to a better understanding of how cultural, religious and political identities are reconfigured across Europe.
CRIS-Team Scopus Importer:2023-04-21